Convergence and Stability for Iterative Schemes Via Integral Conditions - Taresh, Noor Saddam (Al-Nahrain Journal of Science, 2019)
Throughout this work, we introduce some results of convergence, summable almost stability for s-iteration and Picard-Manniterationin Banach space with respect to an integral condition. Also, we study the equivalence between stability of these types of schemes.